2019
DOI: 10.1021/acs.jafc.9b00289
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Organic Compounds Produced by Pseudomonas chlororaphis subsp. aureofaciens SPS-41 as Biological Fumigants To Control Ceratocystis fimbriata in Postharvest Sweet Potatoes

Abstract: The biocontrol activity and chemical composition of the volatile organic compounds (VOCs) produced by Pseudomonas chlororaphis subsp. aureofaciens SPS-41 were investigated. The VOCs inhibited mycelial growth and spore germination in Ceratocystis fimbriata, which causes black rot disease in sweet potato tuber roots (TRs) and showed wide-spectrum antifungal activity against several plant pathogenic fungi. A microscopic examination of C. fimbriata cells suggested morphological changes and a loss of cellular conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(55 citation statements)
references
References 43 publications
2
53
0
Order By: Relevance
“…These three volatiles have good antimicrobial activity and can be produced by a variety of microorganisms, such as S. fimicarius BWL-H1, different Actinobacteria isolates, and Pseudomonas chlororaphis subsp. aureofaciens SPS-41 [20,49,50]. It was found that alcohols showed a noticeably higher antimicrobial activity than esters and ketones in this study, which was consistent with other reports [9,20].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These three volatiles have good antimicrobial activity and can be produced by a variety of microorganisms, such as S. fimicarius BWL-H1, different Actinobacteria isolates, and Pseudomonas chlororaphis subsp. aureofaciens SPS-41 [20,49,50]. It was found that alcohols showed a noticeably higher antimicrobial activity than esters and ketones in this study, which was consistent with other reports [9,20].…”
Section: Discussionsupporting
confidence: 92%
“…The antagonistic assay of VOCs produced by SPS-33 against C. fimbriata was determined according to the previous research [20] with minor modifications. Potato dextrose agar (PDA) medium was added to one side of the I-plates (diameter, 90 mm, volume, 0.07 L), and ISP 2 medium was added to the other side of the same plate.…”
Section: Antagonistic Test Of Vocs Emitted By Sps-33mentioning
confidence: 99%
See 3 more Smart Citations